The Limits of Authority of Regional Heads as Protectors of the Indonesian Red Cross (PMI) under the Red Cross Law - Janggur, Stefanus Kurniadi (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the limits of regional head authority in the PMI management election process so as not to cause conflict or chaos in the region. Methodology/approach: The research method used is a normative approach with a juridical-qualitative method, based on a literature study of laws and regulations, especially Law Number 1 of 2018 concerning the Red Cross and the PMI Statutes/Bylaws. Results/findings: The results of the study indicate that although PMI has a close relationship with the regional government, in the process of appointing and dismissing PMI administrators, regional heads do not have the authority to intervene outside the provisions of PMI's Articles of Association/Bylaws. Article 28 of Law Number 1 of 2018 concerning the Red Cross emphasizes that the organizational structure, management, technical implementing units, authorities, and responsibilities of PMI, as well as procedures for the use of PMI symbols are stipulated in the PMI's articles of association and bylaws in accordance with statutory regulations. Conclusions: Regional heads need to understand that their role is to support, facilitate, and protect the PMI as a humanitarian organization, not to regulate its internal affairs. Regional heads' efforts to maintain synergy with the PMI must be carried out without violating the PMI's independence as part of the International Red Cross and Red Crescent Movement. Limitations: Research on the legal status of the Indonesian Red Cross is still very limited, so journals that can be used as references are very difficult to find. Contribution: As a reference in the PMI management election process so as not to cause conflict or chaos in the region.